2014
DOI: 10.1074/jbc.m114.561704
|View full text |Cite
|
Sign up to set email alerts
|

UBE2E Ubiquitin-conjugating Enzymes and Ubiquitin Isopeptidase Y Regulate TDP-43 Protein Ubiquitination

Abstract: Background: Ubiquitin-modified TDP-43 protein aggregates characterize common neurodegenerative diseases. Results: UBE2E ubiquitin-conjugating enzymes and ubiquitin isopeptidase Y (UBPY) are functional interactors of TDP-43 in cell culture and fly models. Conclusion: Specific regulators of TDP-43 ubiquitination influence its aggregation and neurotoxic properties. Significance: UBE2E and UBPY enzymes may modulate the course of TDP-43 diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
74
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 69 publications
6
74
2
Order By: Relevance
“…Extensive RBM45 pathology was observed in patients with C9ORF72 repeat expansions. RBM45 was subsequently found to bind and colocalize with the C-terminal fragment of TDP-43 implicated in ALS (11), consistent with a role for RBM45 in ALS pathobiology.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Extensive RBM45 pathology was observed in patients with C9ORF72 repeat expansions. RBM45 was subsequently found to bind and colocalize with the C-terminal fragment of TDP-43 implicated in ALS (11), consistent with a role for RBM45 in ALS pathobiology.…”
mentioning
confidence: 60%
“…The accumulation of TDP-43 and other RNA binding proteins in cytoplasmic stress granules may be a more generalized response to eliminate aggregated or mislocalized proteins, whereas RBM45 effectively binds and stabilizes KEAP1 when located at the cytoplasm or stress granules. In addition, RBM45 was recently identified as a TDP-43 binding partner by using a yeast two-hybrid system that used the C-terminal fragment of TDP-43 implicated in ALS (11), suggesting that the two proteins could be functioning as part of similar pathways in disease. More importantly, both RBM45 and TDP-43 have been shown to partially colocalize to cytoplasmic inclusions in motor neurons of ALS spinal cords (9,63).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the E3 ubiquitin ligase Parkin was proposed to ubiquitinate TDP-43, regulating its subcellular transport (Hebron et al, 2013). In D. melanogaster models, the ubiquitin-conjugating enzyme UBE2E3 promotes ubiquitination of TDP-43; in contrast, ubiquitin isopeptidase Y (UBPY) decreased TDP-43 ubiquitination (Hans et al, 2014). Furthermore, knockdown of UBPY promotes formation of insoluble TDP-43 aggregates and induced neurotoxicity in D. melanogaste r (Hans et al, 2014).…”
Section: Neurotoxicity Of Tdp-43/ Fusmentioning
confidence: 99%
“…As many lines of evidence show that TDP-43 ubiquitination provides a strong driving force for the formation of intracellular inclusion bodies in ALS or FTLD, we focused on this modification and investigated whether the ubiquitination of TDP-43 is necessary for the formation of subnuclear InSAC and the processing of IL-6 RNA. In particular, as the ubiquitin-conjugating enzyme UBE2E3 regulates TDP-43 ubiquitination 31 , we generated macrophages stably expressing UBE2E3 shRNA and examined TDP-43 ubiquitination in LPS-stimulated macrophages. We clearly observed that UBE2E3 depletion reduced TDP-43 ubiquitination in the presence of LPS (Fig.…”
Section: Nature Communications | Doimentioning
confidence: 99%